Cetuximab Combined With Sonodynamic Therapy Achieves Dual-Modal Image Monitoring for the Treatment of EGFR-Sensitive Non-Small-Cell Lung Cancer - Qiu, Guanhua; Xue, Lianfang; Zhu, Xiaoqi; Lu, Xiuxin; Liu, Lidong; Wang, Zhonghai; Li, Xiangdong; Huang, Cuiqing; Liu, Junjie (Frontiers in Oncology, 2022)
Background: Blocking signaling by epidermal growth factor receptor (EGFR)，can effectively inhibit the proliferation and differentiation of non-small-cell lung cancer (NSCLC). Additionally, an increasing number of NSCLC patients have treatment limitations caused by EGFR overexpression or mutations. Therefore, we constructed a nanotherapy platform consisting of cetuximab (CTX) to target EGFR-sensitive NSCLC with an iron tetroxide core loading the sound-sensitive agent IR780 for dual-mode imaging diagnosis by combining targeting and sonodynamic therapy (SDT) to reshape the tumor microenvironment (TME), enhance the SDT antitumor effects and improve the therapeutic effects of EGFR sensitivity. Methods: IR780@INPs were prepared by reverse rotary evaporation, CTX was adsorbed/coupled to obtain IR780@INPs-CTX, and the morphology and structure were characterized. Intracellular ROS levels and cell apoptosis first verified its killing effects against tumor cells. Then, a nude mouse lung cancer subcutaneous xenograft model was established with HCC827 cells. A real-time fluorescence IVIS imaging system determined the targeting and live distribution of IR780@INPs-CTX in the transplanted tumors and the imaging effects of the T2 sequence of the INPs by magnetic resonance imaging (MRI) 0 h, 2 h, 4 h and 6 h after administration to confirm drug efficacy. Results: In vitro, US+IR780@INPs-CTX produced a large amount of ROS after SDT to induce cell apoptosis, and significant cell death after live/dead staining was observed. In vivo fluorescence imaging showed the IR780@INPs-CTX was mainly concentrated in the tumor with a small amount in the liver. MRI displayed rapid enrichment of the IR780@INPs into tumor tissue 0h after injection and the T2 signal intensity gradually decreases with time without obvious drug enrichment in the surrounding tissues. In vivo, at the end of treatment, the US+IR780@INPs-CTX group showed disappearance or a continued decrease in tumor volume, indicating strong SDT killing effects. Conclusion: The combination of CTX and SDT is expected to become a novel treatment for EGFR-sensitive NSCLC.